Bending strength and stiffness of structural laminated veneer lumber manufactured from fast-growing Argentinean Eucalyptus grandis - Saviana, Julien (2009)
The present paper reports the results of an investigation regarding the determination of bending strength and stiffness in specimens of laminated veneer lumber (LVL) manufactured from Argentinean Eucalyptus grandis and tested edgewise according to European standards. For this purpose an empirical research project with one sample containing 44 specimens with nominal sizes of 24.3 mm in width, 100 mm in depth and 2.44m in length was carried out. The characteristic strength value was 74 % and 118 % higher, respectively, than those adopted by Argentinean standards for the best strength class of sawn and glued laminated timber of the same species. It was similar to that reported for LVL of Norway spruce and lower than that published for LVL made from Uruguayan Eucalyptus grandis even though in the latter case the reported value was not obtained according to European standards. The modulus of elasticity mean value was 22 % and 14 % higher, respectively, than those adopted by Argentinean standards for the best strength class of sawn and glued laminated timber of the same species. Modulus of elasticity also exhibited a mean value 22 % and 53 % higher, respectively, than those published for LVL manufactured from Norway spruce and Uruguayan Eucalyptus grandis. A relatively low variation of results was found for both strength (COV = 9 %) and modulus of elasticity (COV = 10 %) and the particularly high stiffness/density relation previously published for sawn timber of this Argentinean deciduous species was confirmed by the results of this study. The coefficient of determination (R2) between density and modulus of elasticity was equal to 0.67 whereas R2 reached 0.37 between modulus of elasticity and strength and 0.19 between density and strength.